A generic system for the classification of marble tiles using Gabor filters - Ar, Ilktan; Akgül, Yusuf Sinan (My University, 2008)
This paper presents a marble tile feature extraction system which can be easily used for any classification system. Our system employs Gabor filtering and other image processing techniques to differentiate between different marble textures. As a final product of the system, the percentages of veins, spots, and swirls on the marble images are calculated. Therefore, the presented system can be considered as the core engine of a very portable marble tile classification system. This paper also presents a new verification method which is based on satisfying the inter-expert variability. Experiments on 40 different marble tiles are performed and we concluded that the presented system can be reliably employed for the measurement of the marble features in real life. © 2008 IEEE. © 2009 Elsevier B.V., All rights reserved.
2008 23rd International Symposium on Computer and Information Sciences, ISCIS 2008 -- Istanbul -- 75080
Keywords: Building materials; Feature extraction; Image enhancement; Image processing; Information science; Classification systems; Core engines; Extraction systems; Final products; Gabor filtering; Processing techniques; Verification methods; Marble